A novel POU1F1 pathogenic variant: Two familial case reports with phenotype expansion. Issue 5 (11th August 2021) - Musa, Noha; Elmonem, Mohamed A.; Beetz, Christian; Hafez, Mona; Hassan, Mona; Rolfs, Arndt; Selim, Laila; Elkhateeb, Nour
Abstract : Up: A schematic‐diagram of POU1F1‐gene. Down right: an electrophoretogram of the detected novel pathogenic‐variant in comparison with wild‐type POU1F1 exon‐6 sequence. Down left: Family pedigree of the two‐siblings reported.